Social distancing during COVID-19: threat and efficacy among university students in seven nations. (March 2022) - Guidry, Jeanine P. D.; Perrin, Paul B.; Bol, Nadine; Song, BaoBao; Hong, Cheng; Lovari, Alessandro; Coman, Ioana A.; O'Donnell, Nicole H.; Alkazemi, Mariam; Niu, Jing; Pabian, Sara J. R.; Linn, Annemiek J.; et al.
COVID-19 has been spreading fast worldwide, and until effective and safe vaccines have been widely adopted, preventive measures such as social distancing are crucial to keep the pandemic under control. The study's research questions asked which psychosocial factors predict social distancing behavior and whether there are country-level differences in social distancing? Using the Extended Parallel Process Model (EPPM) as a theoretical lens, we examined the predictive effects of threat and efficacy and demographic variables on adherence to the COVID-19 preventive behavior of social distancing using a survey among an international sample of university students. Using path modeling and analysis of covariance, we confirmed the predictive effects of the EPPM on social distancing behavior. Our final model showed that perceived susceptibility to COVID-19 was both directly and indirectly (through response efficacy) associated with social distancing behavior; that perceived severity of COVID-19 yielded a significant indirect effect on social distancing behavior through both self-efficacy and response efficacy; that perceived susceptibility is indirectly and positively associated with social distancing behavior through response efficacy; and that self-efficacy and response efficacy were directly associated with social distancing behavior. Additionally, there were country-level differences in social distancing. Possible explanations for and implications of these findings are discussed.